Religiosity and Self-Esteem in Relation to Free Sex Behavior Among Generation Z - Aini, Nurul; Khoiryasdien, Andhita Dyorita (Faculty of Psychology, Universitas Semarang, 2025)
This study aims to examine the relationship between religiosity and self-esteem with premarital sex behavior among Gen-Z in Yogyakarta. The study involved 100 respondents with the characteristics of being university students aged 17-24 years, residing in Yogyakarta, and having a tendency toward casual sex behavior. The sampling technique used was Accidental Sampling. The data analysis technique applied in this study was multiple linear regression. The results showed that casual sex behavior is significantly influenced by religiosity and self-esteem (p=0.029<0.05). However, religiosity alone does not have a significant relationship with casual sex behavior (p=0.078>0.05), while self-esteem has a significant relationship with casual sex behavior (p=0.012<0.05). Based on these findings, it is crucial to internalize religious values among Gen-Z. Additionally, building healthy self-esteem should be positively directed through character education that emphasizes self-achievement, thereby reducing the tendency toward casual sex behavior among Gen-Z.